2015
DOI: 10.1371/journal.pone.0123410
|View full text |Cite
|
Sign up to set email alerts
|

Inducible but Not Constitutive Expression of PD-L1 in Human Melanoma Cells Is Dependent on Activation of NF-κB

Abstract: Monoclonal antibodies against immune checkpoint blockade have proven to be a major success in the treatment of melanoma. The programmed death receptor-1 ligand-1 (PD-L1) expression on melanoma cells is believed to have an inhibitory effect on T cell responses and to be an important escape mechanism from immune attack. Previous studies have shown that PD-L1 can be expressed constitutively or can be induced by IFN-γ secreted by infiltrating lymphocytes. In the present study we have investigated the mechanism und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
157
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(171 citation statements)
references
References 43 publications
(45 reference statements)
11
157
2
1
Order By: Relevance
“…14 Furthermore, interferons, especially interferon c, are the most common inducer in adaptive immunemediated PD-L1 upregulation on tumor cells or on tumorinfiltrated leukocytes, including melanoma 15 and ovarian cancer. 2,16 Other inflammatory signaling pathways, including interleukin 4, interleukin 10, vascular endothelial growth factor, granulocyte colony-stimulating factor, and bacterial lipopolysaccharide, have also been shown to induce the expression of PD-L1.…”
Section: Regulation Of Pd-l1 Expression In Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Furthermore, interferons, especially interferon c, are the most common inducer in adaptive immunemediated PD-L1 upregulation on tumor cells or on tumorinfiltrated leukocytes, including melanoma 15 and ovarian cancer. 2,16 Other inflammatory signaling pathways, including interleukin 4, interleukin 10, vascular endothelial growth factor, granulocyte colony-stimulating factor, and bacterial lipopolysaccharide, have also been shown to induce the expression of PD-L1.…”
Section: Regulation Of Pd-l1 Expression In Cancersmentioning
confidence: 99%
“…Using a similar approach with different antibodies, a study showed a higher expression of PD-1/PD-L1 in CD4/CD8 T lymphocytes from chronic lymphocytic leukemia patients when compared with age-matched controls. 49 In addition to peripheral blood cells or lymphocytes, Gowrishankar et al 15 have shown that interferon c induces the upregulation of PD-L1 in a nuclear factor-jB-dependent fashion in 5 different melanoma cell lines and melanoma patient-derived cells using flow cytometry. 15 Furthermore, Andorsky et al 50 documented that PD-L1 is widely expressed by anaplastic large cell lymphoma, whereas it only has limited expression in diffuse large B-cell lymphoma (DLBCL).…”
Section: Strategies To Measure Pd-l1/pd-1 Expression Immunohistochemimentioning
confidence: 99%
“…Because programmed death-1 (PD-1) and PD-L1 blockade have yielded promising clinical effects, understanding the regulatory mechanism of PD-L1 may identify biomarkers and/or develop combinatorial strategies for clinical use (Pardoll, 2012). While transcriptional regulation of PD-L1 via STAT, NF-κB, or NFAT has been reported (Gowrishankar et al, 2015; Huang et al, 2013; Peng et al, 2015), it remains unclear whether and how PD-L1 is posttranscriptionally regulated.…”
Section: Introductionmentioning
confidence: 99%
“…(b) tumor heterogeneity: there are wide intra-and inter-tumoral variations in the expression of PD-L1, indicating that sampling of tumor tissues may also impinge on the outcome of PD-L1 detection [26] ; (c) low specificity: tumors that do not express detectable levels of PD-L1 on the cell surface can also respond to antibodies against PD-1, suggesting that the predictive value of PD-L1 expression may not be uniformly applicable to all types of cancer [26] ; (d) inducible gene expression: PD-L1 can be expressed constitutively or can be induced by IFN- [28,29] secreted by infiltrating lymphocytes or by IL-27 [30] ; and (e ) potential drug resistance: resistance to PD-L1 inhibitors may be a cause of therapeutic failure, however, this has not been well-studied at the current time and needs systematic investigation [26] . PD-L1 has been reported to be modulated by MAPK and PI3K/AkT/mTOR oncogenic signaling pathways [31,32] .…”
Section: Nivolumab Biomarkersmentioning
confidence: 99%